2021
DOI: 10.1007/s11136-021-03040-8
|View full text |Cite
|
Sign up to set email alerts
|

Joint modelling with competing risks of dropout for longitudinal analysis of health-related quality of life in cancer clinical trials

Abstract: Health-related quality of life (HRQoL) is an important endpoint in cancer clinical trials. Analysis of HRQoL longitudinal data is plagued by missing data, notably due to dropout. Joint models are increasingly receiving attention for modelling longitudinal outcomes and the time-to-dropout. However, dropout can be informative or non-informative depending on the cause. MethodsWe propose using a joint model that includes a competing risks sub-model for the cause-specific time-to-dropout.We compared a competing ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Our findings were consistent with prior studies. First, most of the previous studies on joint models, both linear and nonlinear, showed that joint models outperformed separate models in the presence of informative dropout [2428, 30, 32], which was consistent with our key findings. Second, the mix-effects model in the separate models that ignored informative dropout showed over-optimistic estimates for the disease progression trend, corresponding to conclusions drawn in previous studies [2628].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings were consistent with prior studies. First, most of the previous studies on joint models, both linear and nonlinear, showed that joint models outperformed separate models in the presence of informative dropout [2428, 30, 32], which was consistent with our key findings. Second, the mix-effects model in the separate models that ignored informative dropout showed over-optimistic estimates for the disease progression trend, corresponding to conclusions drawn in previous studies [2628].…”
Section: Discussionsupporting
confidence: 91%
“…Second, we considered time to dementia or death as a composite survival outcome instead of modeling them as competing or semi-competing risks. Previous studies showed the competing risks joint model that distinguishes between two causes of dropout may outperform the standard joint model that treats all the dropouts due to different causes equally in general [26, 30, 32]. However, this improvement is most pronounced only when two types of dropouts have substantially different relationships with the longitudinal measures, e.g., one type of dropout is informative and the other one is non-informative, or two competing risks are both informative but oppositely associated with the longitudinal measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We will use mixed effect models and item response models to analyse the repeated measurements, 59 while simultaneously considering joint modelling to account for death as a competing event. 60 …”
Section: Methods and Analysismentioning
confidence: 99%
“…The data collected in the QUALITOP project will benefit from repeated assessments of HRQoL over 18 months, facilitating the study of both individual trajectories over time and the causes and timing of changes in HRQoL. We will use mixed effect models and item response models to analyse the repeated measurements,59 while simultaneously considering joint modelling to account for death as a competing event 60…”
Section: Methods and Analysismentioning
confidence: 99%